2003
DOI: 10.2190/jee0-b7pf-tvpn-ljeu
|View full text |Cite
|
Sign up to set email alerts
|

Defense Mechanisms in a Community-Based Sample of Female Adolescents with Partial Eating Disorders

Abstract: The combined use of immature and neurotic defenses may be associated with a greater risk to develop a partial ED in adolescent females.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 24 publications
3
8
0
1
Order By: Relevance
“…The LSI was designed to assess ego defense mechanisms as conceptualized by Plutchik et al It is a 97-item selfreport questionnaire measuring eight defense mechanisms: compensation, displacement, projection, reaction formation, denial, intellectualization, regression, and repression. This scale was previously found by us to be reliable and valid in adolescent inpatients Fennig et al, 2005;Offer et al, 2000;Stein et al, 2003]. …”
Section: Assessmentmentioning
confidence: 84%
“…The LSI was designed to assess ego defense mechanisms as conceptualized by Plutchik et al It is a 97-item selfreport questionnaire measuring eight defense mechanisms: compensation, displacement, projection, reaction formation, denial, intellectualization, regression, and repression. This scale was previously found by us to be reliable and valid in adolescent inpatients Fennig et al, 2005;Offer et al, 2000;Stein et al, 2003]. …”
Section: Assessmentmentioning
confidence: 84%
“…The study of the psychometric properties of its Greek version showed good convergent validity, adequate internal consistency with Cronbach's alphas 0.60–0.78 and satisfactory test–retest reliability with coefficients 0.69–0.83 for individual defenses studied . LSI has been used in studies with community‐based psychiatric patients and in studies assessing the effectiveness of long‐term psychotherapy ; we have used its Greek version in cancer samples .…”
Section: Methodsmentioning
confidence: 93%
“…Most likely, these figures represented an underestimation of the actual incidence due to incomplete data accrual. Stein, Meged, Bar-Hanin, Blank, Elizur, and Weizman (1997), Stein et al (1999), Stein, Bronstein, and Weizman (2003) evaluated the rate of subsyndromal restrictive and bingeing/purging-type EDs in a series of female 10-12th graders and army recruits according to the combination of a pathological EAT score (>22 points) and the presence of some of the DSM-IV criteria for AN or BN. Between 12 and 21% of the subjects were identified as having a subdyndromal restrictive-type ED, and 8-19% were identified as having a subdyndromal bingeing/purging-type ED.…”
Section: Full and Subsyndromal Eating Disordersmentioning
confidence: 99%